Increased pituitary adenylate cyclase-activating peptide genes expression in the prefrontal cortex in schizophrenia in relation to suicide - Slabe, Zala; Balesar, Rawien A.; Verwer, Ronald W. H.; Drevenšek, Gorazd; Swaab, Dick F. (Frontiers in Molecular Neuroscience, 2023)
Pituitary adenylate cyclase-activating peptide (PACAP) is a stress-related neuropeptide that is produced in several brain areas. It acts by 3 receptors: PACAP type-1 (PAC1), vasoactive intestinal peptide (VIP) -1 and -2 (VPAC1 and 2). Data on polymorphisms in PACAP and PAC1 indicate a relationship of the PACAP system with schizophrenia (SCZ). The prefrontal cortex was chosen to measure PACAP-gene related expression changes, since this is a central structure in the symptoms of schizophrenia (SCZ). We investigated alterations in the expression of the PACAP-related genes by qPCR in the human dorsolateral prefrontal cortex (DLPFC) and anterior cingulate cortex (ACC) of 35 SCZ patients and 34 matched controls in relation to SCZ, suicide, gender and medication. The ACC revealed an upregulation in PACAP, PAC1, VPAC1 and VPAC2 in SCZ suicide (S) completers compared to controls. An increase in PACAP, VPAC1 and VPAC2 expression was also present in the ACC in SCZ-S compared to SCZ patients who died naturally (SCZ-N). In the DLPFC, an increase in PAC1 was found in SCZ-N patients compared to SCZ-S and controls. Moreover, an increase in all PACAP-related genes was present in SCZ-N male patients compared to SCZ-N females. Concluding, expression changes were found in PACAP-related genes in relation to SCZ, suicide and gender. In particular, there was a higher PACAP-related gene expression in SCZ patients in the ACC in relation to suicide and in DLPFC in relation to SCZ. These findings suggest a potential link between PACAP and the pathophysiology of SCZ and suicide. Further research is needed to understand the functional significance and potential clinical applications of these changes.